Coalition and opposition in the perspective of Indonesian constitution - Jamila, Jamila (Journal of Law Science, 2025)
This paper examines the coalition and opposition in the Indonesian constitutional system based on the 1945 Constitution and how political dynamics between them affect executive legislative supervision. In Indonesia's multi-party presidential system, a dominating coalition and a weak opposition make checks and balances difficult. This study combines a normative legal research technique using a normative descriptive approach to map the coalition and opposition and a juridical-analytical approach to examine legislative oversight's legal and practical restrictions. Along with scientific research and comparisons of political systems in other nations, the 1945 Constitution, associated statutes and regulations, and Constitutional Court rulings are employed. The research found that although the 1945 Constitution does not directly govern the coalition and opposition, political practices in Indonesia reveal that the coalition dominates and the opposition is divided and ineffective. The inadequate parliamentary monitoring of executive policies, which are typically formality, is affected. To ameliorate this political dynamic, legal change to formalize opposition regulation, legislative capability, and electoral system simplification are recommended. The research concludes that political and legal change is needed to guarantee Indonesian democracy upholds people's sovereignty and government accountability.